The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1111/sms.12092
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sprint interval training on VO2max and aerobic exercise performance: A systematic review and meta‐analysis

Abstract: Recently, several studies have examined whether low-volume sprint interval training (SIT) may improve aerobic and metabolic function. The objective of this study was to systematically review the existing literature regarding the aerobic and metabolic effects of SIT in healthy sedentary or recreationally active adults. A systematic literature search was performed (Bibliotek.dk, SPORTDiscus, Embase, PEDro, SveMed+, and Pubmed). Meta-analytical procedures were applied evaluating effects on maximal oxygen consumpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

26
198
4
16

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 247 publications
(267 citation statements)
references
References 56 publications
26
198
4
16
Order By: Relevance
“…In this instance, we direct readers to the articulate and comprehensive reviews of Jones and Carter [57], Gibala et al [58] and Sloth et al [20] for a detailed discussion of the underlying physiological adaptations to endurance training and HIT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this instance, we direct readers to the articulate and comprehensive reviews of Jones and Carter [57], Gibala et al [58] and Sloth et al [20] for a detailed discussion of the underlying physiological adaptations to endurance training and HIT.…”
Section: Discussionmentioning
confidence: 99%
“…Gist et al [19] reported a moderate effect (0.69) of sprint interval training (SIT) -classified as form of HIT at the highest end of the intensity spectrum [20] -on VO2max in comparison with no exercise control groups; yet a trivial effect (0.04) when compared with endurance training controls. However, this meta-analysis [19], as well as the recent meta-analyses performed by Weston et al [21] and Sloth et al [20], only addressed the effect of SIT on VO2max. In doing so, these reviews excluded HIT research utilizing longer interval durations and shorter recovery periods.…”
Section: Introductionmentioning
confidence: 99%
“…HIIT has long been used in the athletic setting as a means of enhancing physical performance, [41][42][43][44][45][46] but only more recently in the clinical context for the prevention and management of chronic disease. Thus, the utility of HIIT, relative to MICT, in ameliorating the specific symptoms and adverse effects of those at risk of or afflicted with CVD is not well understood.…”
mentioning
confidence: 99%
“…Recently, high intensity interval training (HIIT) has become popular due to provide rapid aerobic improvements in endurance athletes [16,17]. Also it is well known that these types of aerobic trainings improve performance in well-trained endurance athletes [15,16]. Traditionally, endurance athletes have trained according to approach of high volumes at low intensity and moderate volume at high intensity.…”
Section: Introductionmentioning
confidence: 99%
“…Sandbakk et al (2013) [15], demonstrated that the effectiveness of aerobic high-intensity training on endurance performance and oxygen uptake in national level junior cross-country skiers. Recently, high intensity interval training (HIIT) has become popular due to provide rapid aerobic improvements in endurance athletes [16,17]. Also it is well known that these types of aerobic trainings improve performance in well-trained endurance athletes [15,16].…”
Section: Introductionmentioning
confidence: 99%